Results of treatment of patients with poorly differentiated carcinoma of the thyroid gland - P. A. Isaev; V. V. Polkin; N. V. Severskaya; A. A. Ilyin; A. K. Plugar; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи)
Introduction. Poorly differentiated carcinoma of the thyroid gland (PDTC) is characterised by aggressive, high rate of tumor growth, massive infiltration, early lymphogenous and hematogenous dissemination. Ways to improve treatment outcomes include developing individual treatment programmes. Given the unsatisfactory results of the treatment, the search for combined treatment options is well founded.Materials and methods. An analysis was made of the treatment of PDTC in patients from May 2014 to July 2021. The study included 24 patients aged 22 to 81 years (9 (37.5 %) men and 15 (62.5 %) women). Surgical treatment was performed in 14 (58.3 %) cases. In 8 (33.3 %) cases, a course of radioiodine therapy with a total dose of 3–4 Gbq was performed in the postoperative period. Seven (29.2 %) patients underwent external beam radiation therapy. In 2 (8.3 %) cases, chemotherapy with carboplatin was performed simultaneously with external beam radiation therapy. Four (16.7 %) patients were prescribed lenvatinib. For one reason or another, 9 (37.5 %) patients did not receive treatment.Results. For patients not treated, the overall survival rate was 5.8 ± 0.5 months, for patients treated – 9.6 ± 1.0 months (p <0.00095). According to the index Lenvatinib showed a significant increase in the general group of patients – up to 15 months.Conclusion. Combined treatment in the form of a combination of surgical, radiation and chemotherapeutic methods at PDTC, allows to achieve much higher survival. In order to achieve longer-term stabilization, further research is needed on new ways to enhance the anti-tumor effect of modern drugs.